Volatile metabolic profiling and functional characterization of four terpene synthases reveal terpenoid diversity in different tissues of Chrysanthemum indicum L. (May 2021) - Zhou, Zhiyi; Xian, Jianchun; Wei, Wuke; Xu, Chong; Yang, Jinfen; Zhan, Ruoting; Ma, Dongming
Abstract: Chrysanthemum indicum has long been used in traditional Chinese medicine for its health-promoting benefits. Studies on C. indicum have mainly focused on the flowers. Terpenoid distribution in various parts of the plant and characterization of terpene synthases remain unclear. In this study, volatile metabolic profiling was performed to compare the composition and quantity of terpenoids distributed in the root, stem, leaf, flower bud and flower of C. indicum . The potential for extracting active ingredients from the root, stem, and leaf was also examined. In total, 17 monoterpenoids and 27 sesquiterpenoids were identified. Transcriptome data were used to clone two monoterpene synthases and two sesquiterpene synthases highly expressed in the root. The recombinant proteins of full-length and truncated versions of C. indicum terpene synthase (CiTPS1) produced α-pinene, but the truncated one was catalytically more efficient than the full-length version. No product could be detected when full-length version of CiTPS2 was used for catalyzing GPP, but the truncated one can produce a minor amount of α-pinene. CiTPS3 contributed to the production of three sesquiterpenoids, namely β-farnesene, petasitene, and α-bisabolene. CiTPS4 acted as a difunctional enzyme, contributing to the production of four monoterpenoids and three sesquiterpenoids, including petasitene. The evidence suggests that petasitene and the genes responsible for its biosynthesis were first found in the genus Chrysanthemum. The present findings provide insights into the composition, formation, and regulation of these bioactive compounds. Graphical abstract: Image 1 Highlights: Seventeen monoterpenoids and twenty-seven sesquiterpenoids were identified in C. indicum . Petasitene was only detected in root. Two terpene synthase were found to produce petasitene as one of its products. Some gene-to-terpene landscapes associated with different tissues are described. The potential for extraction of active ingredients from root, stem and leaf are discussed.